Self-regulated learning in higher education : strategies adopted by computer programming students - Pedrosa, Daniela (2016)
To help students overcome their learning difficulties in the transition from entry-level to advanced computer programming, developing an appropriate set of learning strategies, the SimProgramming teaching approach has been adopted at the University of Trás-os-Montes e Alto Douro (Portugal). This approach is based on four conceptual foundations: businesslike learning environment, self-regulated learning, co-regulated learning, and formative assessment. In this approach the students develop an activity based on problem-based learning, with a specific set of tasks based on those four conceptual foundations. The approach was implemented in two courses from the second and third curricular years of the bachelor programmes in Informatics Engineering and Information & Communication Technologies. We conducted semi-structured interviews with students (n=32) at the end of the courses, to try to identify the students’ strategies for self-regulation of learning in the activity developed within the SimProgramming approach. The main strategies identified were: organization, planning, time management, identification of difficulties, resolution of the difficulties encountered, work review, identification of the factors that influenced their motivation, and structure of the environment. The factors influencing the motivation most often identified by students were the impact of the assessment in the final course grade, the completion of the course, learning, skills development, and teamwork. Generally, students applied strategies to solve the difficulties, in particular by searching for social help and information search. Procrastination was also often identified by students. Strategies of time management, transformation of information, in-depth review, self-reflection, and self-evaluation were referenced scantily. We found that students changed some of their strategies from one course edition to the next. We conclude by recommending the development of educational practices to help students review their work, treat and process the information they find, conduct self-reflection and self-evaluation of their performance during tasks, adopt concentration strategies, and become aware of their specific difficulties.